Perceptual coding of audio signals - Teh, Do Hui. (2009)
This thesis presents the research work done to improve the implementability of the ISO/MPEG (International Standard Organisation/Moving Picture Experts Group) audio coding algorithm. The main concept behind this audio coding algorithm is the use of a psychoacoustic model as the basis for removing audio signals which are irrelevant to the human ear. The model is examined in detail and it is then implemented and used in the development of a perceptual performance evaluation tool. The results of the perceptual performance evaluation tool are compared with the mean opinion scores of the Stockholm subjective listening tests conducted by the ISO/MPEG members.